2016
DOI: 10.24198/pjd.vol28no3.13675
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethanol extract of Sarang Semut plant (Hypnophytum formicarum) towards Angiogenesis for wound healing after tooth extraction: Experimental research on Marmot (Cavia cobaya)

Abstract: Introduction: Tooth extraction causing injuries, to accelerate wound healing was given medication. Drugs commonly used for wound healing after tooth extraction is povidone iodine act as bacteriostatic for all germs. Excessive use of povidone iodine can cause side effects such as itching, pain in the area around the wound, swelling and dermatitis, so it sought a safe substitute drugs derived from herbs. One of the herbs are often used by people in the Mentawai Islands is a Sarang Semut's root species of Hypnoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…9 By contrast, research conducted by Putri and Ismardianita found that the orally administered Hydnophytum formicarum plant extract at a dose of 4.65 mg was able to significantly increase angio genesis. 13 Wound healing with minimal to no scarring oc curs in the oral mucosa and the fetal skin in the uterus, pre senting less angiogenesis as compared to wound healing in the skin; however, the capillaries become mature more rapidly. Many new capillaries in the healing wounds in the skin do not function effectively.…”
Section: Discussionmentioning
confidence: 99%
“…9 By contrast, research conducted by Putri and Ismardianita found that the orally administered Hydnophytum formicarum plant extract at a dose of 4.65 mg was able to significantly increase angio genesis. 13 Wound healing with minimal to no scarring oc curs in the oral mucosa and the fetal skin in the uterus, pre senting less angiogenesis as compared to wound healing in the skin; however, the capillaries become mature more rapidly. Many new capillaries in the healing wounds in the skin do not function effectively.…”
Section: Discussionmentioning
confidence: 99%
“…The migration and proliferation of fibroblast cells together with the growth of new blood vessels responsible for the supply of oxygen-rich blood and nutrients, as the marker of the fibroplastic phase. [ 1 28 ]…”
Section: Discussionmentioning
confidence: 99%